Conventional and unconventional ubiquitination in plant immunity. (10th February 2017) - Zhou, Bangjun; Zeng, Lirong
Summary: Ubiquitination is one of the most abundant types of protein post‐translational modification (PTM) in plant cells. The importance of ubiquitination in the regulation of many aspects of plant immunity has been increasingly appreciated in recent years. Most of the studies linking ubiquitination to the plant immune system, however, have been focused on the E3 ubiquitin ligases and the conventional ubiquitination that leads to the degradation of the substrate proteins by the 26S proteasome. By contrast, our knowledge about the role of unconventional ubiquitination that often serves as non‐degradative, regulatory signal remains a significant gap. We discuss, in this review, the recent advances in our understanding of ubiquitination in the modulation of plant immunity, with a particular focus on the E3 ubiquitin ligases. We approach the topic from a perspective of two broadly defined types of ubiquitination in an attempt to highlight the importance, yet current scarcity, in our knowledge about the regulation of plant immunity by unconventional ubiquitination.